Efficiency of fluid organomineral fertilizer with pig slurry in nitrogen and phosphorus availability - Grohskopf, Marco André; Cruz, Caio Vilela; Ferreira-Eloy, Natália Rodrigues; Fernandes, Dirceu Maximino; Büll, Leonardo Teodoro; Corrêa, Juliano Corulli (Revista de Ciências Agroveterinárias, 2020)
The use of pig slurry (PS) in fluid fertilizer formulation, for nitrogen (N) and phosphorus (P) supply, consists of an innovative technology due to this waste reuse in the environment. The objective of this study was to assess the agronomic efficiency of fluid organomineral fertilizers with PS concerning solid and fluid forms of soluble minerals as a source of N and P in a Typic Quartzipsamment (Entisol) and Typic Hapludox (Oxisol). Two experiments were carried out in a greenhouse, with three sequential cultivations in a completely randomized design. Experiment 1: was composed of N and presented the treatments Without-Nitrogen (N-W), solid mineral (N-SM), fluid mineral (N-FM), and fluid with PS (N-FO). Experiment 2: was composed of P and presented the treatments Without-Phosphorus (P-W), solid mineral (P-SM), fluid mineral (P-FM), and fluid with PS (P-FO). The fertilizer N-FO presented a lower N use efficiency by crops in Entisol when compared to the granular fertilizer N–SM, but a higher efficiency in Oxisol. For phosphorus, the fertilizer P-FO was more efficient concerning the solid mineral source P-SM in both Oxisol and Entisol soils. Fluid organomineral fertilizer with PS demonstrated to be a promising source of N and P for crop fertilization, especially in sandy soils, however, more studies are needed with this fertilizer type and its effect on plants and into acid soils of variable charges.